2018
DOI: 10.1007/s10948-018-4599-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inhomogeneous Phase on the Critical Temperature of Smart Meta-superconductor MgB2

Abstract: of the luminescent inhomogeneous phase doping samples increased and then decreased as increasing current.Keywords smart meta-superconductor MgB2 · Y2O3:Eu 3+ nanosheets · Inhomogeneous phase·Applied electric field·TC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In addition, similar experimental results were obtained by replacing Y 2 O 3 :Eu 3+ with Y 3 VO 4 :Eu 3+ flakes 46 . Meanwhlie, results also indicated that the T C can be changed by adjusting the Y 2 O 3 :Eu 3+ concentration and EL exciting current 47 . However, there are some problems need to improve in the experiments.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, similar experimental results were obtained by replacing Y 2 O 3 :Eu 3+ with Y 3 VO 4 :Eu 3+ flakes 46 . Meanwhlie, results also indicated that the T C can be changed by adjusting the Y 2 O 3 :Eu 3+ concentration and EL exciting current 47 . However, there are some problems need to improve in the experiments.…”
Section: Introductionmentioning
confidence: 89%
“…However, there are some problems need to improve in the experiments. Y 2 O 3 :Eu 3+ particles or flakes tended to agglomerate during the preparation process and its EL intensity was weak 4447 . The quality of commercial MgB 2 was poor and its superconducting transition width ( ΔT ) is 4.6 K 46,47 , further experiment and improvement will be needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The external field added during the measurement of the T c of SMSC with a four-probe method can excite the inhomogeneous phases to generate EL, achieving the purpose of strengthening the Cooper pairs, resulting the change of T c in macroscopic. A SMSC is a material whose T c can be adjusted and improved by the stimulus of external field, which is a new property and cannot be achieved by traditional doping with a second phase [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Our group subsequently conducted a series of studies, mainly using MgB 2 as the base superconducting material and Y 2 O 3 :Eu 3+ as the base EL material [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the doping of Y 2 O 3 :Eu 3+ EL materials increases the T C of MgB 2 . We believe that the Y 2 O 3 :Eu 3+ materials generate an EL under the action of an external electric field and that EL energy injection promotes the formation of Cooper pairs; the T C of MgB 2 is improved via EL [ 35 , 36 , 37 , 38 , 39 ]. At the same time, a smart meta-superconductor B(P)SCCO consists of the B(P)SCCO matrix and an inhomogeneous phase Y 2 O 3 :Eu 3+ or Y 2 O 3 :Eu 3+ +Ag was constructed in BSCCO superconductors.…”
Section: Introductionmentioning
confidence: 99%